An Update in Breast Cancer Screening and Management. (March 2016) - Warrier, Sanjay; Tapia, Grace; Goltsman, David; Beith, Jane
This article provides an overview of the main controversies in a number of key areas of breast cancer management. Relevant studies that have contributed to guide the treatment of this heterogeneous disease in the field of breast screening, surgery, chemotherapy and radiotherapy are highlighted. Mammography and ultrasound are the main methods of breast screening. MRI and tomosynthesis are emerging as new screening tools for a selected group of breast cancer patients. From a surgical perspective, oncoplastic techniques and neoadjuvant chemotherapy are improving cosmetic results in breast-conserving surgery. For high-risk patients, controversies still remain regarding prophylactic mastectomies. Finally, the appropriate management of the axilla continues evolving with the increasing role of radiotherapy as an alternative treatment to axillary dissection.